Manager's job satisfaction and possible implications in budget management: the case of public universities in Peru - Arnao Rondán, Raymundo Ildefonzo (2021)
The purpose of this research was to determine the level and main characteristics of managerial job satisfaction in Peru's public universities, and the progress of budget execution in these institutions, as well as the correlation between job satisfaction and the progress of budget execution. To measure job satisfaction, a survey was applied to a sample of managers in specialized areas of the central administration of the institution (elected officials were excluded), using a questionnaire generated in a pilot experience and with the corresponding statistical verification of its reliability. Recognizing that there is great heterogeneity among public universities with the amount of budget, number of workers and number of students, among other dimensions, it was possible to form five strata, using as grouping criteria the total budget and the budget of projects for the 2017-2019 triennium, for each case.  Through these groups, the heterogeneous progress in budget execution among public universities is demonstrated, with differences in projects being more accentuated; also, the predominance of diversity of levels and characteristics in terms of the job satisfaction of their managers is evidenced. Finally, taking universities as units of analysis, a moderate positive correlation was found between job satisfaction and budget execution progress (both at the total and project levels). This implies that it is moderately likely that greater job satisfaction is accompanied by better progress in budget execution.